Critical analysis of valganciclovir dosing and renal function on the development of cytomegalovirus infection in kidney transplantation. Issue 6 (9th September 2013) - Posadas Salas, M.A.; Taber, D.J.; Chua, E.; Pilch, N.; Chavin, K.; Thomas, B.
Abstract Background Cytomegalovirus (CMV) infection is one of the most common and important opportunistic infections following kidney transplantation. It causes significant morbidity and mortality. Valganciclovir (VGCV) is the drug of choice for prophylaxis to prevent CMV infection. Methods We conducted a post‐hoc analysis of a randomized controlled trial in 187 kidney transplant recipients to evaluate the impact of VGCV dosing and renal function on the development of CMV infection. Results and conclusion The results demonstrate that the following variables were independent risk factors for the development of CMV infection: high‐risk CMV serostatus (donor positive/recipient negative; hazard ratio [HR] 1.4, 95% confidence interval [CI] 1.46–5.28, P = 0.002); anti‐thymocyte globulin induction therapy (HR 2.1, 95% CI 1.08–4.07, P = 0.028); higher mean tacrolimus trough concentration (HR 1.4, 95% CI 1.09–1.74, P = 0.007); creatinine clearance <60 mL/min (HR 3.4, 95% CI 1.64–6.85, P = 0.001); and body weight >80 kg (HR 2.1, 95% CI 1.05–4.37, P = 0.037). VGCV dosing was appropriate for most patients, in those who did and did not develop CMV infection. These results strongly suggest that the currently recommended dose adjustments of VGCV dosing based on estimated renal function calculated using ideal body weight may underestimate the renal function of overweight patients and indirectly result in underexposure of overweight patients to VGCV. Based on these findings, further VGCV pharmacokinetic analyses are warranted in kidney transplant recipients with moderate‐to‐severe renal dysfunction.